IN SILICO MOLECULAR MODELING AND DOCKING STUDIES OF HERBAL COMPOUND MEDIATED INHIBITION OF ÎšÎ² KINASEÎ² (INHIBITOR OF ÎšÎ² KINASE SUBUNIT Î²) FOR OSTEOARTHRITIS TREATMENT - Subramani, Baskaran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: This study was intended to investigate and characterize the phytoconstituents of plant herbs and inhibitors, evaluate its anti-osteoarthritis (OA) and anti-inflammatory potential under in silico conditions. Methods: Docking studies were performed to find out the maximum interaction between design ligands and selected five proteins using Schrodinger Software NY. Structures of selected proteins were downloaded from protein data bank. Results: Morin, salubrinal, icariin, and chondroitin sulfate, and sesamol have higher binding energy than other compounds. Based on these properties out of 9 compounds we have selected 5 best-docked and compounds selected were molecular dynamics simulation with inhibitor of ÎºÎ² kinase subunit (IKK) Î². Arg20, Leu21, Thr23, Lys44, Glu61, Glu97, Cys99, Lys106, Asp145, Asn150, andAsp166 were actively involved in H-bond interaction with ligands. Each compound has different binding modes, which reflects the difference of interacting residues with different functional groups. Morin has better interaction than other compounds. Either Cys99 or Lys44 found predominantly in most of the complex except in Î²-ecdysterone whereas both found interacting with morin. Conclusion: The results revealed out that the herbal compounds can inhibit the IKKÎ² protein. The virtual screening yielded five potential IKKÎ² inhibitors: Morin, salubrinal, icariin, and chondroitin sulfate, and sesamol. This inhibitor shows good interaction, energy, and pharmacophoric activity and will be suitable for further experiments of an anti-OA target.